Higher Parental Age and Lower Educational Level are Associated with Underweight among Preschool Children in Terengganu, Malaysia - Mohamad, Rose Haniza; Abdul Hakim, Bibi Nabihah; Mitra, Amal K.; Shahril, Mohd. Razif; Wan Mohamed, Wan Mohd. Izani; Syed Saadun Tarek Wafa, Sharifah Wajihah Wafa; Burgermaster, Marissa; Jan Mohamed, Hamid Jan (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2022)
This cross-sectional study aimed to investigate the determinants of underweight among preschool children. A total of 218 preschool children were enrolled. Their sociodemographic data were collected using self-reported questionnaires whilst body weight and height were measured, recorded and the BMI for-age z-score was calculated using WHO AnthroPlus software. Of all preschool children participants, 47.7% were male and 53.3% were female. Most of them were Malays (99.5%), aged 4 to <5 years (40.8%) and came from low-income household (92.7%). Overall, the prevalence of underweight, normal, overweight and obese was 17.9%, 73.8%, 4.6% and 3.7% respectively. The underweight prevalence was higher than the national prevalence (13.7%). Of all parent participants, 12.4% were male and 87.6% were female. Most of them aged 30−39 years (55.5%) and did not hold a degree (89.4%). Multivariate logistic regression showed that parental age and their level of education were the determinants of childhood underweight. The risk of being underweight increased with the age of parents (p=0.033) and lower level of education of parents (p=0.042). In conclusion, this study found that underweight among preschool children was mainly associated with parental factors. Hence, designing a special nutritional intervention program involving older parents and lower education levels could overcome this problem.